Patient-important outcomes in systematic reviews: Poor quality of evidence - Yordanov, Youri (PLoS One, 2018)
BACKGROUND: Cochrane reviewers are strongly encouraged to evaluate the quality of evidence for the most important outcomes by using the GRADE approach and to report these results in a Summary of Findings (SoF) table. We aimed to assess whether outcomes reported in the SoF table of Cochrane reviews could be considered patient-important outcomes (PIOs) and the quality of the available evidence for these outcomes. METHODS: We performed a methodological review of Cochrane reviews published between March 2011 and September 2014. For a random sample of Cochrane reviews reporting a SoF table, we extracted all outcomes reported in this table and evaluated whether they could be considered PIOs (i.e., mortality, other clinical events, adverse events, function, pain, quality of life and therapeutic decisions). Then, we collected the quality of evidence for every outcome in these SoF tables. RESULTS: We included 290 reviews issued by 47 of the 53 Cochrane Review Groups. Every SoF table included a median of 5 outcomes, for a total of 1414 outcomes; 1089 (77%) could be considered PIOs. Almost all reviews (n = 278, 96%) included at least one PIO in their SoF table. The quality of evidence for the outcomes was high for 12% (n = 168), moderate for 28% (n = 402) and low or very low for 45% (n = 640). Less than one quarter of reviews (n = 63) included at least one PIO with high-quality evidence that favoured a benefit of the experimental intervention evaluated in half of them (n = 34 reviews). CONCLUSIONS: Many outcomes reported in the SoF table of recent Cochrane reviews can be considered PIOs. However, the quality of available evidence remains limited for these outcomes.